Застосування методу двобічних наближень до розв’язання першої крайової задачі для нелінійного рівняння теплопровідності - Василишин, К. В. (ХНУРЕ, 2021)
The first boundary value problem for a nonlinear heat equation on an interval with a power coefficient of heat conductivity and power functions of heat sources is considered. For its numerical solution, was proposed to use the two-sided approximates method.
Keywords: метод двобічних наближень; задача теплопровідності; перша крайова умова